Coerência interna em pesquisas em Psicologia e contribuições à Educação : análise da produção no período de 2011-2015 no periódico Psicologia Escolar e Educacional - Prezenszky, Bruno Cortegoso (Universidade Federal de São Carlos, 2017)
Subjects in present information society are required to master school content, skills and competencies. Such mastering must be assured by the education centers, what configures the instrumental dimension of school education. Throughout history, scientific knowledge production in the Psychology area has been contributing with research, practice, theory and policies in Education, but recently, there have been observed tensions in such relation, as well as a decrease in the presence of Psychology in the educational area. Also, recent studies have pointed out different problems related to scientific knowledge production in the educational area, such as lack of rigor, weak theoretical grounding and lack of consistency within a study. As an element that helps in analyzing the consistency of a study, here is proposed the internal methodological coherence, indicated by the coherence between the goals of a study, its method and its results. Given such elements, the present study aimed to identify, characterize and analyze recent academic production in Psychology as it relates to Education regarding contributions to teaching and instrumental learning, as of its production’s frequency, internal methodological coherence of scientific studies conducted and potential contributions to the educational field. It was searched, in the journal Psicologia Escolar e Educacional, articles produced between 2011 and 2015 that addressed the instrumental dimension of education (n=41), and it was conducted the analysis of 18 of them that explicitly indicated contributions to educations. It were identified their themes and educational level to which they referred, and the internal coherence of the studies between their aims, method and results. Contributions to the instrumental dimension of education indicated by the authors were also identified. The main results found include that the most frequent theme in the studies was reading and writing, and the most frequent educational level was basic education, whereas kindergarten and Youth and Adult Education were not mentioned in any paper. As of the methods used, eight research designs were identified, and the most frequent was the correlational design. The analysis indicated that, with few exceptions, studies show adequate usage of methods and coherence between proposed objectives, implemented method and results obtained in the analyzed studies, which may indicate quality of produced knowledge. The main contributions reported by the authors of the studies referred to teaching and learning of reading and writing.
Keywords: Psicologia educacional; Metodologia de pesquisa; Dimensão instrumental; Educational psychology; Research methodology; Instrumental dimension; CIENCIAS HUMANAS::EDUCACAO